2017
DOI: 10.3389/fphar.2017.00384
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Reimbursement Recommendations by European HTA Agencies: Is There Opportunity for Further Alignment?

Abstract: Introduction: In Europe and beyond, the rising costs of healthcare and limited healthcare resources have resulted in the implementation of health technology assessment (HTA) to inform health policy and reimbursement decision-making. European legislation has provided a harmonized route for the regulatory process with the European Medicines Agency, but reimbursement decision-making still remains the responsibility of each country. There is a recognized need to move toward a more objective and collaborative reimb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(76 citation statements)
references
References 10 publications
1
66
1
2
Order By: Relevance
“…Nevertheless, subsequent research has already shown that HTA jurisdictions can be classified to one archetype for one product and to another for another product, once more underlining the problems with generalizing HTA recommendations. 23 The many changes in HTA processes within jurisdictions over time and the consistent international variations in HTA practices indicate that there is not yet a uniformly applicable "best practice" for HTA. Of course, different countries have different values, which can result in different preferences for reimbursement (eg, automatic reimbursement at regulatory approval or a more closed system), and HTA systems have often been shaped by political and historic arguments (eg, the UK cancer drug fund).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, subsequent research has already shown that HTA jurisdictions can be classified to one archetype for one product and to another for another product, once more underlining the problems with generalizing HTA recommendations. 23 The many changes in HTA processes within jurisdictions over time and the consistent international variations in HTA practices indicate that there is not yet a uniformly applicable "best practice" for HTA. Of course, different countries have different values, which can result in different preferences for reimbursement (eg, automatic reimbursement at regulatory approval or a more closed system), and HTA systems have often been shaped by political and historic arguments (eg, the UK cancer drug fund).…”
Section: Discussionmentioning
confidence: 99%
“…As country-specific economic inputs were aligned with local HTA submission guidelines, the model inputs and results of our cost-effectiveness analysis reflected differences between the healthcare systems and economic wealth of the four countries analyzed 58,69,70 . Total costs were slightly higher for denosumab than for ZA across all four countries, which were driven by higher acquisition costs for denosumab vs ZA; the latter is now available as a generic version [47][48][49]51 .…”
Section: Discussionmentioning
confidence: 99%
“…The diverging results could also be due to the fact that the scope (comparators and cost considerations) and the methodology used vary across countries [47]. Allen et al [48] found similar results in a study on national reimbursement decisions in nine countries for more than 100 new active substances approved by the European Medicines Agency.…”
Section: Comparison On Hta and Decision Outcomes In Different Settingsmentioning
confidence: 97%